2011
DOI: 10.1016/j.devcel.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Complement Fragment C3a Controls Mutual Cell Attraction during Collective Cell Migration

Abstract: SummaryCollective cell migration is a mode of movement crucial for morphogenesis and cancer metastasis. However, little is known about how migratory cells coordinate collectively. Here we show that mutual cell-cell attraction (named here coattraction) is required to maintain cohesive clusters of migrating mesenchymal cells. Coattraction can counterbalance the natural tendency of cells to disperse via mechanisms such as contact inhibition and epithelial-to-mesenchymal transition. Neural crest cells are coattrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
336
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(358 citation statements)
references
References 32 publications
17
336
1
4
Order By: Relevance
“…It is noteworthy that half of the isolated cells actually migrated backward toward the endogenous plate ( Fig. 2 E and F), suggesting that they might be attracted by the group, as recently described in neural crest cells (24). Unfortunately, analysis of cells transplanted laterally or posteriorly to the plate could not confirm this point, as these cells stayed immobile, probably lacking a permissive environment for their migration.…”
mentioning
confidence: 67%
“…It is noteworthy that half of the isolated cells actually migrated backward toward the endogenous plate ( Fig. 2 E and F), suggesting that they might be attracted by the group, as recently described in neural crest cells (24). Unfortunately, analysis of cells transplanted laterally or posteriorly to the plate could not confirm this point, as these cells stayed immobile, probably lacking a permissive environment for their migration.…”
mentioning
confidence: 67%
“…5 b). C3a signaling promotes cell-cell interactions, thus contributing to cohesion of the neural crest cell collective, and is necessary for efficient chemotaxis toward SDF-1 (Carmona-Fontaine et al, 2011). In summary, a variety of mechanisms cooperate in migration of CNC cells.…”
Section: Contact Inhibition Of Locomotion: Polarizing the Collectivementioning
confidence: 97%
“…5 b), the placodal cells adjacent to the neural crest (Theveneau et al, 2010. A third mechanism of autocrine chemotaxis, named coattraction, directly opposes CIL-mediated cell scattering: neural crest cells secrete the complement factor C3a and express its receptor C3aR (Carmona-Fontaine et al, 2011). The C3a/C3aR system acts in an autocrine fashion to attract neural crest cells together, thus counterbalancing the dispersion promoted by CIL (Fig.…”
Section: Contact Inhibition Of Locomotion: Polarizing the Collectivementioning
confidence: 99%
“…Indeed, the expression of complement molecules at the gastrula/ early neurula stage and organ-specific expression patterns during organogenesis were observed in Xenopus laevis (McLin et al, 2008). Furthermore, a recent study showed that Xenopus neural crest cells are coattracted via the complement fragment C3a and its receptor C3aR (Carmona-Fontaine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%